Cellulose Nanocrystal (CNC)–Latex Nanocomposites: Effect of CNC Hydrophilicity and Charge on Rheological, Mechanical, and Adhesive Properties. Issue 3 (12th October 2020) - Pakdel, Amir Saeid; Niinivaara, Elina; Cranston, Emily D.; Berry, Richard M.; Dubé, Marc A.
Abstract: Cellulose nanocrystals (CNCs), a sustainable nanomaterial, are in situ incorporated into emulsion‐based pressure‐sensitive adhesives (PSAs). Commercially available CNCs with different surface hydrophilicity and surface charge (CNC101 and CNC103 from CelluForce) are used to explore their role in PSA property modification. Viscosity measurements and atomic force microscopy reveal differences in degree of association between the CNCs and the latex particles depending on the surface properties of the CNCs. The more hydrophilic and higher surface charge CNCs (CNC101) show less association with the latex particles. Dynamic strain sweep tests are used to analyze the strain‐softening of the nanocomposites based on CNC type and loading. The CNC101 nanocomposites soften at lower strains than their CNC103 counterparts. This behavior is confirmed via dynamic frequency tests and modeling of the nanocomposites' storage moduli, which suggest the formation of CNC aggregates of, on average, 3.8 CNC101 and 1.3 CNC103 nanoparticles. Finally, PSA properties, i.e., tack, peel strength, and shear strength, simultaneously increase upon addition of both CNC types, although to different extents. The relationship between the PSA properties and CNC surface properties confirms that the less hydrophilic CNCs lead to improved CNC dispersion in the PSA films and therefore, enhance PSA properties. Abstract : Cellulose nanocrystals (CNCs) with different surface properties are in situ incorporated in emulsion polymerization of pressure‐sensitive adhesives (PSAs). CNCs with less hydrophilicity and lower surface charge better associate with latex particles, form shorter aggregates (enhanced dispersion), and produce high peel strength PSAs. The more hydrophilic CNCs form longer aggregates and lead to elevated shear strength (highly elastic PSAs).